An efficient three-dimensional solid finite element dynamic analysis of reinforced concrete structures. - Spiliopoulos, K. V.
Most of the finite element analyses of reinforced concrete structures are restricted to two-dimensional elements. Three-dimensional solid elements have rarely been used although nearly all reinforced concrete structures are under a triaxial stress state. In this work, a three-dimensional solid element based on a smeared fixed crack model that has been used in the past mainly for monotonic static loading analysis is extended to cater for dynamic analysis. The only material parameter that needs to be input for this model is the uniaxial compressive strength of concrete. Steel bars are modelled as uniaxial elements and an embedded formulation allows them to have any orientation inside the concrete elements. The proposed strategy for loading or unloading renders a numerical procedure which is stable and efficient. The whole process is applied to two RC frames and compared against existing experiments in the literature. Results show that the proposed approach may adequately be used to predict the dynamic response of a structure.
Keywords: Dynamic analysis; Non-linear RC analysis; Smeared crack model; 3D solid finite element; Seismic loading; RC concrete frames